Coding region variant 186H/R in Exon 4 of APOBEC3G among individuals of Western India. Issue 5 (8th February 2016) - Singh, HariOm; Marathe, Shruti; Nain, Sumitra; Nema, Vijay; Angadi, Mansa; Bapat, Shradha; Pawar, Jyoti; Ghate, Manisha; Sahay, Seema; Gangakhedkar, Raman R.
Abstract : The allelic variations in the AIDS restriction genes have been associated with the acquisition of HIV‐1 and its progression. The distribution of antiviral gene variants significantly differs between populations. Therefore, we aimed to evaluate the distribution of variant allele of 186H/R in exon4 of APOBEC3G between HIV infected individuals and healthy controls among western Indian.In the present cross‐sectional study, we enrolled a total of 153 HIV‐infected patients confirmed and 156 unrelated healthy individuals. Polymorphism for 186H/R in exon4 of APOBEC3G gene was genotyped by PCR‐RFLP. With the frequency of 186HR heterozygous genotype of APOBEC3G was found to be 13% in healthy controls and none in HIV infected cases. The frequency of 186HH common genotype of APOBEC3G was observed higher in HIV infected individuals compared with healthy controls (100% vs 91.7%). The variant genotype 186RR in APOBEC3G was not found in both the groups. The frequency of 186R allele of APOBEC3G was found 4.16% in healthy controls and nil in HIV‐infected cases. The frequency of 186H allele of APOBEC3G was found to be higher in HIV‐infected cases compared with healthy controls (100% vs 95.83%). The frequency of 186R allele in exon4 of APOBEC3G was found to be 4.16% in healthy controls. This observation differs from the previous report published from North India stating the absence of 186R allele of APOBEC3G in the North Indian individuals. The variant 186H/R in exon4 of APOBEC3G was neither associated with risk of acquisition of HIV‐1 nor its progression.